Pathogen genomics and phage-based solutions for accurately identifying and controlling Salmonella pathogens - Lopez-Garcia, Angela V.; AbuOun, Manal; Nunez-Garcia, Javier; Nale, Janet Y.; Gaylov, Edouard E.; Phothaworn, Preeda; Sukjoi, Chutikarn; Thiennimitr, Parameth; Malik, Danish J.; Korbsrisate, Sunee; Clokie, Martha R. J.; Anjum, Muna F. (Frontiers in Microbiology, 2023)
Salmonella is a food-borne pathogen often linked to poultry sources, causing gastrointestinal infections in humans, with the numbers of multidrug resistant (MDR) isolates increasing globally. To gain insight into genomic diversity of common serovars and their potential contribution to disease, we characterised antimicrobial resistance genes, and virulence factors encoded in 88 UK and 55 Thai isolates from poultry; presence of virulence genes were detected through an extensive virulence determinants database complied in this study. Long-read sequencing of three MDR isolates, each from a different serovar was used to explore the links between virulence and resistance,. To augment current control methods, we determined sensitivity of isolates to twenty-two previously characterised Salmonella bacteriophages. Of the 17 serovars included Salmonella Typhimurium and its monophasic variants were most common, followed by S. Enteritidis, S. Mbandaka, and S. Virchow. Phylogenetic analysis performed on Typhumurium and monophasic variants, which was most frequent, showed poultry isolates were generally distinct from pigs. Resistance to sulfamethoxazole and ciprofloxacin was highest in isolates from the UK and Thailand, respectively, with 17-18% of all isolates being MDR. We noted >90% of MDR isolates were likely to carry virulence genes as diverse as srjF, lpfD, fhuA, and stc operon. Long-read sequencing revealed presence of global epidemic MDR clones in our dataset, indicating they are possibly widespread in poultry. The clones included MDR ST198 S. Kentucky, harbouring a Salmonella Genomic Island-1 (SGI)-K; the European ST34 S. 1,4,[5],12:i:- harbouring SGI-4 and mercury-resistance genes; and a S. 1,4,12:i:- isolate from the Spanish clone harbouring an MDR-plasmid. Results of testing of all isolates to a panel of bacteriophages showed variable sensitivity to phages, with STW-77 found to be most effective. It lysed 37.76% of the isolates, including serovars important for human clinical infections: S. Enteritidis (80.95%), S. Typhimurium (66.67%), S. 1,4,[5],12:i:- (83.3%), and S. 1,4,12: i:- (71.43%). Therefore, our study revealed combining genomics and phage sensitivity assays holds promise for accurately identifying and providing bio-controls for Salmonella, to prevent its dissemination in poultry flocks and through the food chain to cause infections in humans.